PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR IPS (Studi Eksperimen Siswa Kelas IV SDN 007 Pulau Lawas Kecamatan Bangkinang) - Hayati Fitri Hayati Fitri; Erlisnawati Erlisnawati '; Zetra Hainul Putra Hainul Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the result of social studies grade IV SDN 007 Pulau Lawas low. The purpose of this study was to determine the effect of the application of cooperative learning model Think Pair Share (TPS) on the results of social studies grade IV SDN 007 Pulau Lawas District of Bangkinang. This research is a class by using a quasi-experimental design with nonrandomized control group pretest-posttest design. This research was conducted in two classes, namely the control class (IVB) and the experimental class (IVA). Grade control using conventional learning model and the experimental class using learning model TPS. From the analysis of the average pretest experiment class 47,3 and control 49. While the results of the average post-test analysis of the experimental class 66,8 and control 51,73. To determine whether there is a significant difference between the experimental class and control class t test was used. Based on the pretest obtained test t thitung = - 0,239 < ttabel = 2,021, it can be concluded that Ho is accepted, the average score of pretest results of study no significant differences. While the t test at posttest obtained thitung = 2,975 > t tabel = 2,021 it can be concluded that Ha is accepted and there is a significant difference between the two classes. Based on the N-Gain experimental class increased by 0.39 and increased by 0.02 grade control. The influence of cooperative learning model Think Pair Share (TPS) is 64% of the students' learning outcomes IPS experimental class. At the end of this study are a good influence on the implementation of cooperative learning model TPS.Keywords : Cooperative Learning Model Think Pair Share (TPS ) , IPS Learning Outcomes.